Sturge-Weber syndrome with massive macroglossia and anterior neck space infection- a case report and review of literature - Iftikhar, Namirah; Osama Khalid; Uzma Ghori (Journal of the Pakistan Medical Association, 2024)
Sturge- Weber syndrome (SWS), is a rare neuro-cutaneous angiomatosis which affects male and females alike. The clinical manifestations include angiomas, haemangiomas of the lips, tongue and palatine region. The oral manifestations are usually unilateral and are susceptible to bleed. Patients can also present with macroglossia and maxillary bone hypertrophy which can lead to malocclusion of the oral cavity. Food accumulation due to occlusion can cause growth of bacteria which can intensify infections and can cause gingival hyperplasia. A case of a middle-aged 39 year old female was reported in the Ziauddin Hospital, Karachi on 2nd of February,2022 with the presenting complaints of intermittent fever and drowsiness for 10 days. On examination she had massive tongue enlargement, drooling, malocclusion, difficulty in eating and breathing. —Continue